Fractalkine shedding is mediated by p38 and the ADAM10 protease under pro-inflammatory conditions in human astrocytes. Issue 1 (December 2016) - O'Sullivan, Sinead; Gasparini, Fabrizio; Mir, Anis; Dev, Kumlesh
Abstract Background The fractalkine (CX3CR1) ligand is expressed in astrocytes and reported to be neuroprotective. When cleaved from the membrane, soluble fractalkine (sCX3CL1) activates the receptor CX3CR1. Although somewhat controversial, CX3CR1 is reported to be expressed in neurons and microglia. The membrane-bound form of CX3CL1 additionally acts as an adhesion molecule for microglia and infiltrating white blood cells. Much research has been done on the role of fractalkine in neuronal cells; however, little is known about the regulation of the CX3CL1 ligand in astrocytes. Methods The mechanisms involved in the up-regulation and cleavage of CX3CL1 from human astrocytes were investigated using immunocytochemistry, Q-PCR and ELISA. All statistical analysis was performed using GraphPad Prism 5. Results A combination of ADAM17 (TACE) and ADAM10 protease inhibitors was found to attenuate IL-1β-, TNF-α- and IFN-γ-induced sCX3CL1 levels in astrocytes. A specific ADAM10 (but not ADAM17) inhibitor also attenuated these effects, suggesting ADAM10 proteases induce release of sCX3CL1 from stimulated human astrocytes. A p38 MAPK inhibitor also attenuated the levels of sCX3CL1 upon treatment with IL-1β, TNF-α or IFN-γ. In addition, an IKKβ inhibitor significantly reduced the levels of sCX3CL1 induced by IL-1β or TNF-α in a concentration-dependent manner, suggesting a role for the NF-kB pathway. Conclusions In conclusion, this study shows that the release of soluble astrocytic fractalkine is regulated by ADAM10 proteases with p38 MAPK also playing a role in the fractalkine shedding event. These findings are important for understanding the role of CX3CL1 in healthy and stimulated astrocytes and may benefit our understanding of this pathway in neuro-inflammatory and neurodegenerative diseases.